Understanding Event Management through Public Relations Prisms: The Implications and the Emerged Paradigms - CHUKWU, Obinna Johnkennedy (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: As a crucial component of public relations, event management has evolved significantly over the years, presenting numerous challenges and opportunities for organizations. This paper explores the intricate relationship between event management and public relations, analyzing its implications and examining the emerging paradigms in this dynamic field. The paper delves into the fundamental connection between event management and public relations. It highlights how events are a powerful tool for organizations to enhance their brand image, engage with key stakeholders, and achieve strategic communication objectives.Methodology: Through an extensive literature review, the paper elucidates the role of event management in fostering brand recognition, reputation management, and relationship building. Furthermore, the paper scrutinizes the implications of effective event management on organizational success. Findings:It examines how well-executed events can strengthen stakeholder trust, increase media visibility, and generate positive public sentiment. An essential aspect of this paper involves exploring the emerged paradigms in event management through public relations prisms. Implication:The paper identifies and analyzes contemporary trends and innovative approaches that have reshaped event planning and execution; this includes integrating technology and digital platforms to enhance event experiences, leveraging social media for real-time engagement and amplification, and adopting sustainability practices to align events with environmental and social responsibilities.